Living anionic polymerization of 4‐diphenylphosphino styrene for ABC triblock copolymers. Issue 1 (12th September 2016) - Schultz, Alison R; Chen, Mingtao; Fahs, Gregory B; Moore, Robert B; Long, Timothy E
Abstract: Living anionic polymerization of 4‐diphenylphosphino styrene (DPPS) achieved unprecedented poly(S‐ b ‐I‐ b ‐DPPS) ABC triblock copolymers with predictable molecular weights and narrow polydispersities. In situ Fourier transform infrared spectroscopy probed the anionic polymerization, monitoring vinyl disappearance during sequential monomer addition for kinetic analysis. Varying the concentration of reinforcing, polystyrenic external blocks enabled diverse compositions with tunable thermomechanical properties and tailored morphology. Dynamic mechanical analysis confirmed the presence of microphase separation in the triblock copolymers and revealed a broad temperature range ( ca 100 o C) for a plateau region and onset of flow temperatures above 100 o C. Small‐angle X‐ray scattering and atomic force microscopy collectively revealed solid state morphologies of the triblock copolymers and probed phase separation at the nanoscale. Well‐defined poly(S‐ b ‐I‐ b ‐DPPS) ABC triblock copolymers with tunable structure − property relationships now permit phosphorus‐containing thermoplastic elastomers for emerging applications. © 2016 Society of Chemical Industry Abstract : Living anionic polymerization of 4‐diphenylphosphino styrene (DPPS) achieved unprecedented poly(S‐ b ‐I‐ b ‐DPPS) ABC triblock copolymers with predictable molecular weights and narrow polydispersities, permitting phosphorus‐containing thermoplastic elastomers for emerging applications.